[Can we find predictive factors of postoperative vomiting after day surgery?] - Lemos, P. (2008)
Abstract A retrospective analyses of patients submitted to surgery on a day basis was made through our database. The goal of the study was to identify risk factors of postoperative vomiting associated to day surgery. 2115 patients operated between January 2003 and November 2004 on our day surgery unit were included. 70 patients (3,3%) suffered at least on episode of postoperative vomiting. Several factors were analysed: age, sex, surgical speciality, ASA physical status, anaesthetic technique and the duration of anesthesia. Chi-Square Test was used for testing each factor individually. Differences were considered significant when p <0,05. Logistic regression was then used to identify the multivariate association strength of these factors. The female sex (Odds ratio =4,94) and the duration of anesthesia when longer than 180 minutes (Odds ratio =8,13), had been associated to a higher incidence of postoperative vomiting, while loco-regional technique (Odds ratio = 0,15) and sedation with local anaesthesia (Odds ratio =0,09) had been associated with a lower incidence. Authors evidence the importance of the identification of postoperative vomiting risk factors that will allow us to establish better guidelines on postoperative nausea and vomiting prophylaxis in these patients and to improve the quality of our clinical care and the satisfaction of our patients. Através da análise do registo informatizado de dados dos doentes operados em regime de ambulatório, os autores procuraram identificar factores de risco que se encontrassem associados a uma maior incidência de vómitos no pós-operatório (VPO). Incluíram-se 2115 doentes submetidos a cirurgia entre Janeiro de 2003 e Novembro de 2004, tendo 70 doentes sofrido pelo menos um episódio de VPO (3,3%). Foram consideradas variáveis a analisar, a idade, o sexo, a especialidade cirúrgica, o estado físico (ASA), a técnica anestésica e a duração da anestesia. Procedeu-se à análise estatística de cada factor individualmente através da aplicação do χ2, seguindo-se a utilização de uma regressão logística para identificar a força de associação multivariável desses factores. O sexo feminino (Odds ratio =4,94) e a duração da anestesia quando superior a 180 minutos (OR =8,13), associaram-se a uma maior incidência de VPO enquanto a técnica loco-regional (OR =0,15) e a sedação com anestesia local (OR =0,09) se associaram a uma menor incidência daqueles. Os autores evidenciam a importância deste tipo de trabalhos na identificação de factores de risco que possam levar à criação de escalas de risco que orientem com maior racionalidade económica, a intervenção terapêutica profiláctica das náuseas e vómitos no pós-operatório.